Transmit-array antenna design for broadband backhaul 5G communications at WiGiG band - Matos, S.; Costa, J. R.; Fernandes, C. A.; Nachabe, N.; Luxey, C.; Titz, D.; Gianesello, F.; Del-Río, C.; Arboleya-Arboleya, A.; Teixeira, J.; Garnero, J.; Vizzari, J. (14th European Conference on Antennas and Propagation (EuCAP 2020), Proceedings, 2020)
A cost-effective transmit-array (TA) antenna design framework is presented and experimentally validated for a 5G backhaul application at the WiGiG band. The antenna is composed of a discrete dielectric lens (DDL) fed by a horn, specifically designed for this application. Both the TA and feed are fabricated using additive manufacturing. Metal coating and Fuse Deposition Modeling are employed for the horn and TA fabrication, respectively. Simple design rules are devised to quantify the bandwidth of this type of antennas as function of the aperture dimension and focal distance . Based on this framework a compact TA antenna ( ⁄=.) than can comply with typical specifications for 5G backhaul links at WiGiG band (minimum gain of 30 dBi from 57 to 66 GHz) is designed.